Vertical distributions and columnar properties of the aerosols during different seasons over Kattankulathur (12.82oN, 80.04oE): A semi-urban tropical coastal station. (1st July 2021) - Ananthavel, Aravindhavel; Mehta, Sanjay Kumar; Reddy, T.V. Ramesh; Ali, Saleem; Rao, D. Narayana
Abstract: Seasonal characteristics of the aerosols over Kattankulathur (12.83° N, 80.04° E) is studied using Micro Pulse Lidar observations during 2016–2018 and Cloud Aerosol Lidar and Infrared Pathfinder Satellite Observation, Moderate Resolution Imaging Spectroradiometer and Ozone Monitoring Instrument datasets during 2006–2018. The vertical distribution of the aerosols is characterized as the steep decrease with altitude nearly exponentially up to 2–3 km during the northeast (NE) monsoon and winter seasons mainly dominated by clear marine and polluted continental aerosols. While it gradually decreases with altitude up to 4–5 km during pre-monsoon and southwest monsoon (SW) seasons mainly dominated by dust aerosols. The mean aerosol loadings near the surface are 0.38 km −1 during NE monsoon and winter, 0.30 km −1 pre-monsoon, and 0.22 km −1 during SW monsoon seasons. Such difference in the seasonal distribution of aerosol loading is mainly attributed to the difference in surface insolation, convection, long-range transport, and the atmospheric boundary layer (ABL) structure and dynamics. The ABL contributes 61%, 46%, 38%, and 63% of the overall aerosol optical depth (AOD) during the winter, pre-monsoon, SW monsoon, and NE monsoon seasons, respectively. The AOD shows a substantial seasonal variation with two local maxima during May and October and minima during January and July. The maximum and minimum AOD is found to be 0.59 ± 0.16 and 0.4 ± 0.05, respectively. The Angstrom exponent (AE) (fine mode fraction (FMF)) shows a marked seasonal variation with a maximum value of 0.84 (0.60), indicating the dominance of finer particles during winter and minimum value of 0.54 (0.27), indicating dominance coarse particles during SW monsoon. The AE and UV aerosol index values suggest that Kattankulathur is mainly characterized by large-sized absorbing aerosols (30%) such as dust mixture and sea salt particles. Small-sized non-absorbing aerosols such as biogenic aerosols are rarely (<1%) observed. Highlights: Seasonal characteristics of the vertical distributions of aerosols are reported over Kattankulathur for the first time. The mean aerosol loadings near the surface are 0.4 km -1 during NE monsoon, winter, and pre-monsoon and 0.3 km -1 during SW monsoon. The maximum and minimum aerosol optical depths are found to be 0.59 ± 0.16 and 0.4 ± 0.05, respectively. Clear marine and polluted continental aerosols dominate during NE monsoon and winter, while dust aerosols during pre-monsoon and SW monsoon.